Discrete and canonical quantum variables - Ruzzi, M.; Machado, S.S.L.; Galetti, Diogenes [UNESP] (Sociedade Brasileira de Física, 2003)
A connection betweend discrete, Cartesian and angular quantum variables is obtained and discussed.